Innovative social networks modelling for population simulation. (16th July 2019) - Massei, Marina; Matteo, Riccardo Di
Today social networks are an important element of society that requires developing new models as well as guidelines to create interoperable simulators covering these aspects. These new simulators are expected to enable researches and developments focused on people reactions to simulated events via social networks. This research area results are promising, however, it is necessary to address also several challenging issues including proper development of new conceptual models as well as validation and verification processes and definition of human behaviour modifiers. The authors present a new methodological framework for modelling individuals and populations by means of web social networks, in order to reproduce their dynamics. The article proposes to create interoperable models of social networks along with a real case study related to training and decision making process for authorities. The paper includes experimentations over a complex scenario where human factors and social networks play a crucial role.